A Uniform Practice for Conceptualizing and Communicating Food‐Energy‐Water Nexus Studies. Issue 5 (10th May 2019) - Gunda, T.; Tidwell, V. C.
Abstract : There is growing interest in nexus research: energy‐water, energy‐water‐land, and more recently food‐energy‐water. Motivating this movement is the recognition that the dynamics and feedbacks that constitute these nexuses have been overlooked in the past but are critical to the planning and management of these interacting elements. Formal reviews have identified gaps in current studies. In this commentary, we highlight additional oversights that are hindering integration of findings in nexus studies, notably usage of imprecise terminology to describe analyses, a failure to close the loop by linking production with corresponding waste streams, and exclusion of dynamics linking diverse constituent elements. Equally lacking from current nexus studies is a consistent protocol for communicating the conceptual basis of our studies. To fill this gap, we draw on diverse perspectives and fields to propose a comprehensive and systematic framework that can guide the model conceptualization phase of nexus studies. We also present a standardized documentation practice (similar to one utilized by the agent‐based modeling community) to facilitate communication of nexus studies. These initiatives can improve our ability to account for and communicate the nuanced, food‐energy‐water nexus interactions in a consistent manner, which is necessary to better inform risk analysis and avoid decisions with unintended consequences and hidden costs to society. Key Points: Imprecise descriptions used by current FEW nexus studies make it challenging to understand findings Incorporating wastes and dynamic feedbacks in nexus interactions is critical for completeness A consistent framework for conceptualizing and communicating FEW studies is proposed